The acute effects of a stretching and conditioning exercise protocol for the lower limbs on gait performance- a proof of concept and single-blind study - Santinelli, Felipe B. [UNESP]; Prieto Silveira-Ciola, Aline [UNESP]; Moreno, Vinicius C. [UNESP]; Kuroda, Marina H. [UNESP]; Barbieri, Fabio A. [UNESP] (Frontiers, 2024)
Background: Due to improvement in movement performance, post-activation performance enhancement (PAPE) may open new possibilities to improve gait performance. However, no study has attempted to translate this phenomenon into walking. Therefore, the study aimed to test whether acute stretching followed by a conditioning exercise can improve subsequent gait performance in healthy adults. Research question: Can an exercise protocol subsequently improve gait performance? Methods: Sixteen individuals walked four 10-m trials (in each period) before and after 7 min of an exercise protocol composed of stretching (focusing on the lower limb) and a conditioning exercise (standing calf-raise wearing a vest of 20 kg). Gait spatialtemporal parameters and muscle activity of tibialis anterior and gastrocnemius medialis and lateralis muscles were obtained by a 3D-motion system and wireless electromyography, respectively. Before and after the exercise protocol, kinematic and muscle activity parameters were compared by a one-way ANOVA and the Wilcoxon signed-rank test, respectively. Results: After the exercise protocol, the participants walked with a faster step velocity (p < 0.018) and with a lower step duration (p < 0.025). Also, higher peak muscle activity (p < 0.008) and low-frequency (p < 0.034) activation of the anterior tibial muscle after the exercise protocol were observed. Significance: In conclusion, the protocol improves the stability and the muscles’ efficiency during gait, contributing to a new approach to enhancing gait rehabilitation programs.
Keywords: conditioning exercise; locomotion; muscle activity; post-activation performance enhancement (PAPE); stability